TIPOLOGI KONSTRUKSI RUMAH TRADISIONAL “FALA GABA-GABA” SEBAGAI PERWUJUDAN BANGUNAN HEMAT ENERGI - Endah Harisun; M Amrin Ms Conoras; Hafid Saefudin (Journal of Science and Engineering, 2019)
Fala Gaba-gaba is a traditional house with most of the building material coming from sago trees. Where sago trees are plants that grow a lot in eastern Indonesia including Maluku, North Maluku and Papua. Made from natural materials, coupled with an opening arrangement that adapts to the local climate makes the traditional house "fala gaba-gaba" as one of the energy-efficient buildings. The purpose of this study is to describe the construction of a traditional house "fala gaba-gaba" from the foundation, body and roof of the building associated with Energy Saving Buildings. The conclusion that can be drawn is one of the embodiments of energy-efficient buildings, this can be proven by placing the orientation of the building towards the direction of the wind and sun, wall and floor materials used, placement of openings that can maximize lighting and natural acceleration and building type which is a stilt house can maximize lighting and natural air.